The music during century of the masses (Music and society) 2 (Nóema, 2012)
Strauss in the U.S. His relations with Hitler and Goebbels. The diffusion of the book and mass-production. The Beatles among technology, popular culture, aesthetic and the revolutionary generation.
Keywords: Ross; Marzo Magno; Venice; capital of the book; Massimo Carboni; Analphabeatles